До історії зоогеографічних досліджень Полтавщини - Рогожа, М.М. (Питання історії науки і техніки, 2008)
В статье рассмотрена история становления и развития зоогеографических
исследований, проведенных на территории Полтавщины, и их особенности. Показана
роль полтавских и других ученых-естествоиспытателей в этих исследованиях и их
вклад в изучение хребетных животных региона, круг их научных интересов. The article is focused on the history of formation and development of zoogeographical
researches at the Poltava region. The role of scientists from Poltava and other
areas in these researches is outlined. Contribution of these scientists in the investigation of
Poltava region vertebrates and their fields of scientific interests are marked.